(untitled) - Allen, Christopher (Illinois, USA, 2004)
This text provides hands-on instruction to relational database design and management using Oracle examples. The proven format features step-by-step tutorials, end-of-chapter reviews, practice questions, key term lists, and lab projects.
Keywords: Relational databases,SQL (Computer program language),Cơ sở dữ liệu thông dụng,SQL (ngôn ngữ chương trình máy tính)